Personalized Health Systems—Past, Present, and Future of Research Development and Implementation in Real-Life Environment - Lewy, Hadas; Barkan, Refael; Sela, Tomer (Frontiers in Medicine, 2019)
Personal health systems (PHS) designed to provide the individual a tailored care while enabling the healthcare system deliver a high quality care to large populations and maintain a sustainable system. Solutions using Electronic Health Records (EHR) data including predictive models for risk of disease onset and deterioration serve the care provider to identify and treat patients for chronic disease and preventive care. These tools are well accepted by doctors and were proven to improve health outcomes and cost reduction. Integrated tele-care programs were implemented for comorbid patients showing improved clinical outcomes self-management and QoL however different patients' population benefits in a different ways from the care plan and thus a continuous evaluation, service adaptation in real life environment set with clear outcome measures is required to yield best results. The challenge of PHS today is to acquire patient generated data (PGD), clinical, behavioral and patient reported outcomes (PROs) for PHS development that can be combined EHR data. Some initiatives of healthcare organizations (HMOs) in Israel demonstrate how this goal can be achieved in relatively small efforts by using stepwise and agile approach for services implementation that improve service and enable adoption and adaptation of the service in the short term while collecting data for advanced PHS development in the long term. This approach, combined with programs and incentive payments at the national level creates an environment for setting infrastructure and collaboration between healthcare, academia and industry for research, development and implementation of future PHS